2017
DOI: 10.1038/s41699-017-0027-1
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Protective molecular passivation of black phosphorus

Abstract: A correction to this article has been published and is linked from the HTML version of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…As shown in Figure e,f, a N 1s peak was identified in eda-BP, which was generated by the EDA treatment . The spectrum’s doublet peaks at 129.9 and 130.8 eV might be ascribed to P 2p 3/2 and P 2p 1/2 , respectively, which is consistent with crystalline BP. Additionally, a faint oxidation signal of O–PO was seen in BRP at 133.0 eV, which might be a result of the reactive eda-BP being partially reoxidized during the preparation procedure. FTIR (Figure g) analysis revealed that no apparent EDA peaks such as the C–N bond (1065 cm –1 ) or the N–H bond (1608 cm –1 ) developed after EDA activation, validating the low EDA concentration in eda-BP, and the absorption bands at about 1124 cm –1 correspond to the P–O stretching vibrations produced during the oxidation of BP .…”
Section: Resultsmentioning
confidence: 84%
“…As shown in Figure e,f, a N 1s peak was identified in eda-BP, which was generated by the EDA treatment . The spectrum’s doublet peaks at 129.9 and 130.8 eV might be ascribed to P 2p 3/2 and P 2p 1/2 , respectively, which is consistent with crystalline BP. Additionally, a faint oxidation signal of O–PO was seen in BRP at 133.0 eV, which might be a result of the reactive eda-BP being partially reoxidized during the preparation procedure. FTIR (Figure g) analysis revealed that no apparent EDA peaks such as the C–N bond (1065 cm –1 ) or the N–H bond (1608 cm –1 ) developed after EDA activation, validating the low EDA concentration in eda-BP, and the absorption bands at about 1124 cm –1 correspond to the P–O stretching vibrations produced during the oxidation of BP .…”
Section: Resultsmentioning
confidence: 84%
“…Indeed, many types of photodetectors based on black phosphorus have been demonstrated, operating in the visible and the near-IR bands. ,, These photodetectors show high responsivity and low dark currentthanks to BP’s bandgap, which is a significant advantage over grapheneand a very high response speed . Although the chemical stability of black phosphorus is a concern as it reacts with water and oxygen and quickly degrades when exposed to air, , BP can be passivated or concealed, , after which the BP devices can be preserved over a very long time without discernible degradation in device performance. Another challenge faced by BP is the lack of method to grown it in large area, which is under development …”
mentioning
confidence: 99%
“…Moreover, b-P and b-AsP sandwiched between hBN layers exhibits long term stability in ambient conditions and even under the irradiation of strong laser [45,68,85,86]. In addition to covering b-P with hBN or oxide by atomic layer deposition, organic molecules also are a good choice to prevent degradation and keep long term device stability [13,16,55,69,87,88]. There are many encapsulation methods that have demonstrated long term effectiveness and can be used to device development in the future.…”
Section: Materials Stabilitymentioning
confidence: 99%